2009
DOI: 10.1097/brs.0b013e318188386a
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion With a Locked Plate and Wedged Graft Effectively Stabilizes Flexion-Distraction Stage-3 Injury in the Lower Cervical Spine

Abstract: Anterior cervical fusion with a wedged graft and a rigid constrained (locked) plate can effectively stabilize the nonosteoporotic cervical spine after complete posterior element injury when excessive ROM is prevented (for example, by the use of postoperative external immobilization). Even when the construct is subjected to higher moments, adequate stability can be achieved when physiologic preload is present. Osteoporosis and lack of sufficient preload due to poor neuromuscular control may affect long-term scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…We have almost always encountered grossly disrupted discs during anterior surgery; therefore, we prefer the anterior approach. Biomechanical investigations have demonstrated that ACDF with plating can effectively stabilize the non-osteoporotic cervical spine after complete posterior element injury19). In this study, all patients underwent successful reduction and stabilization through the anterior approach, and there was no instability at the last follow-up.…”
Section: Discussionmentioning
confidence: 70%
“…We have almost always encountered grossly disrupted discs during anterior surgery; therefore, we prefer the anterior approach. Biomechanical investigations have demonstrated that ACDF with plating can effectively stabilize the non-osteoporotic cervical spine after complete posterior element injury19). In this study, all patients underwent successful reduction and stabilization through the anterior approach, and there was no instability at the last follow-up.…”
Section: Discussionmentioning
confidence: 70%
“…Highly detrimental effects are expected in such a severe compression, but this case presented an unusual sparing of the upper limbs, and the patient was totally continent throughout while his lower limbs displayed significant symptoms secondary to compression. Bilateral facet dislocation of C4 through C7 creates instability and frequently is associated with quadriplegia [14]. The sparing of the upper limbs indicates that, even with 70% subluxation, injury to the cord and nerve roots was incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior fixation provides a more rigid fixation compared to anterior stabilization; however, the rigidity provided by anterior fixation is significantly higher than in an intact motion segment 12. The anterior approach in addition provides direct access to the cord and the compressive elements and has a lower incidence of post-surgical kyphosis 13…”
Section: Discussionmentioning
confidence: 99%
“…More recently, global fusion has been recommended in translation rotational injuries associated with end-plate fractures and burst or tear drop fractures;1215 however good fusion rates (85-90%) have been achieved following anterior fusion and fixation in flexion, distraction, and translation rotational injuries 1216…”
Section: Discussionmentioning
confidence: 99%